2012
DOI: 10.1111/j.1464-410x.2011.10893.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic indicators for upper tract urothelial carcinoma after radical nephroureterectomy: the impact of lymphovascular invasion

Abstract: Study Type – Prognosis (case series) Level of Evidence 4 What's known on the subject? and What does the study add? In an array of urological and non‐urological malignancies, lymphovascular invasion (LVI) is a pathological feature known to be associated with adverse outcomes for recurrence and survival. For some cancers, LVI has therefore been incorporated into American Joint Committee on Cancer TNM staging algorithms. This study presents an analysis of the impact of LVI in upper urinary tract urothelial carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 25 publications
0
22
2
Order By: Relevance
“…In the present study, the CSS rate was higher than in other studies; the 5-year CSS rate of patients with sarcopenia was 77.9% in our study, 57.1% in that by Ishihara et al, and 69% in that by Fukushima et al. Another reason was that the strong prognostic indicator of LVI [13][14][15] was not evaluated by Ishihara et al. In our study, LVI was the only independent predictor for cancer-specific death and sarcopenia independently predicted…”
contrasting
confidence: 54%
“…In the present study, the CSS rate was higher than in other studies; the 5-year CSS rate of patients with sarcopenia was 77.9% in our study, 57.1% in that by Ishihara et al, and 69% in that by Fukushima et al. Another reason was that the strong prognostic indicator of LVI [13][14][15] was not evaluated by Ishihara et al. In our study, LVI was the only independent predictor for cancer-specific death and sarcopenia independently predicted…”
contrasting
confidence: 54%
“…Similarly, in another study conducted by Sakano et al [8] involving 502 patients, patients with advanced pT stage accounted for 42% (38% of patients with pure UTUC and 73% of patients with UTUC with CVH). The proportions of advanced pT stage of other multi-institutional studies also ranged from 30.6% to approximately 35% [13,[22][23][24]. Furthermore, patients with UTUC with CVH were at a significantly higher risk of cancer-specific mortality, disease recurrence, and overall death compared with patients who had pure UTUC, as demonstrated by Kaplan-Meier survival curves.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, we could not perform meta-analysis for PFS and OS because only 1 study was eligible for PFS [11] and OS [12], respectively. Only 2 studies were evaluated for the impact of race on CSS.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1,037 articles were excluded upon examination of the titles and abstracts, while the full text of 315 articles was evaluated. In accordance with all previously mentioned inclusion criteria, a final selection of 79 articles was made [912, 1892]; any discrepancies between the two evaluations were resolved. The PRISMA flow chart depicting the process for the systematic literature search and selection of the studies is shown in Figure 5.…”
Section: Methodsmentioning
confidence: 99%